'Butta 12', a two‐rowed malting barley adapted to the California Central Valley with proven floor‐malting success and craft brewer acceptance. Issue 3 (2nd September 2020) - Gallagher, Lynn W.; Silberstein, Ron; Prato, Linda; Vogt, Herb
Abstract: 'Butta 12' (Reg. no. CV‐371, PI 692639) is the first malting barley ( Hordeum vulgare L.) released by the University of California to complete plant‐scale malting evaluation and to be brewed successfully by scores of craft brewers. In cooperation with Admiral Maltings, Alameda, CA, Butta 12 has been malted and marketed primarily under the names Gallagher's Best, Feldblume, and Admiral Pils for all‐malt brewing and distilling. Butta 12 combines good malting quality, adequate disease resistance, and good agronomic performance to provide a local maltster with a grower‐accepted local source of malting barley. Kilning variables produced a wide range of flavors. Additionally, Butta 12 and a related malting cultivar 'UC Tahoe' are nonproducers of glycosidic nitrile, which is an advantage for their use by distillers. With no initial California two‐rowed malting barley germplasm as a starting point, it took over 20 yr of breeding work to combine favorable alleles for malting quality from the Oregon State University barley improvement program with increased disease resistance from the barley breeding program of International Center for the Improvement of Agriculture in the Dry Areas (ICARDA)/International Center for Maize and Wheat Improvement (CIMMYT), Mexico. The focus on disease resistance was necessary because several barley diseases in California prevent the direct introduction of malting cultivars into California's Central Valley from the northern tier of U.S. states and Canada.